Functional Urban Areas in Colombia - Sanchez-Serra, Daniel (OECD Regional Development Working Papers, 2016)
This paper applies the OECD-EU methodology to identify the functional urban areas (FUAs) in Colombia. Using the municipal boundaries, population grid data and inter-municipalities commuting flows from the 2005 population census, the paper identifies 53 FUAs accounting for 27 million people, or 63% of the national population. The resulting FUAs are then compared with the existing national definition (Misión del Sistema de Ciudades) and the legally constituted metropolitan areas in Colombia. Finally, using the OECD-EU methodology already applied to OECD countries, the eight largest FUAs in Colombia are compared with the 281 largest FUA in OECD countries, through a set of economic, social and environmental indicators. The application of the OECD-EU methodology allows to identify the whole system of urban areas in Colombia, with the same criterion; it thus provides a complementary tool to the national and city government to better plan and design future urban policy strategies. For example, this paper finds that metropolitan areas in Colombia have smaller commuting areas relative to OECD average and that improvements in the transport infrastructure may strengthen the economic integration of Colombian metropolitan areas